2015
DOI: 10.1016/j.tate.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Professional development at the local level: Necessary and sufficient conditions for critical colleagueship

Abstract: h i g h l i g h t sInvestigation of conditions associated with teachers' in-depth discussions. Focus on teacher communities of inquiry in a professional development initiative. Using unique methodological approach: Qualitative Comparative Analysis. Single purpose was a necessary condition associated with in-depth discussion. Coach questions and connecting theory and practice were also associated conditions. a b s t r a c t This paper examines factors that contributed to critical conversations in teacher commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 69 publications
0
34
1
Order By: Relevance
“…In these teams, teachers learned about and discussed the nuances of FA and supported one another in implementing these practices in their classrooms. See Kintz et al (2015) and Cisterna et al (2016) for more information about the PD model and features.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these teams, teachers learned about and discussed the nuances of FA and supported one another in implementing these practices in their classrooms. See Kintz et al (2015) and Cisterna et al (2016) for more information about the PD model and features.…”
Section: Methodsmentioning
confidence: 99%
“…We worked with four science teachers from two different focal learning teams that were selected purposely for more intensive study by our larger research program (Kintz et al, 2015). We were able to observe the PD meetings of these two focal learning teams for at least 1 year, and we had evidence of the teachers' engagement in the program.…”
Section: Participants and Data Sourcesmentioning
confidence: 99%
“…Van Veen et al, 2012). More recent studies confirm this finding (e.g., Carrillo, Maasen van den Brink, & Groot, 2016;Coenders & Verhoef, 2018;DeNeve & Devos, 2016;Kintz, Lane, Gotwals, & Cisterna, 2015). Furthermore, several studies suggested that feedback from peers elicits reflection on the part of the feedback receiver (Showers & Joyce, 1996) and, moreover, that feedback and reflection were important characteristics of effective PTL activities.…”
Section: Conclusion and Discussionmentioning
confidence: 79%
“…Situative approaches underpin the PLD that groups or communities of teachers are engaged in when they participate in collaborative inquiry into their own teaching and its impact on learners. Such groups are variously described as communities of learners (MOE, 2017c), collaborative teacher inquiry teams (Ermeling, 2010), communities of inquiry (Kintz, Lane, Gotwals, & Cisterna, 2015), and professional learning communities (PLC) (Hipp & Huffman, 2010), or may be groups that engage in practitioner inquiry (Newman & Mowbray, 2012).…”
Section: Collaborative Approaches To Professional Learning and Develomentioning
confidence: 99%